Studies on the Indian Gharial (Gavialis gangeticus Gmelin) (Reptilia, Crocodilia) V: Preliminary Observations on Maternal Behaviour - Singh, Lala A. K.; Bustard, H. R. (Indian Forester, 1977)
Breeding female crocodiles often exhibit socio-maternal behaviours like nest-guarding, breaking the unhatched eggs between the jaws, carrying the hatchlings to the water and protecting them from predators and other crocodiles. A twelve feet long female gbarial, Gavialis gangelieus (Gmelin), inhabiting the Satkoshia Gorge of River Mahanadi, Orissa had laid 25 eggs in April 75, which were transferred for hatchery incubation, restoring the neat to its original. Daily records on the post laying behaviour of the female showed that it returned to the nest eleven times during the incubation period. Visits were most frequent during the period when hatching would normally be expected. These later movements were presumably for releaoillg the hatchlings from the nest. It seems unlikely that gharials exhibit other aspects of maternal behaviour involving direct handling of hatchlings and unhatched eggs because the jaw structure is not suitable and the location of the eyes make this extremely difficult, if not impossible.